Nursing Administration: Watson's Theory of Human Caring. (April 2022) - Gunawan, Joko; Aungsuroch, Yupin; Watson, Jean; Marzilli, Colleen
Watson's human caring theory is widely used in nursing clinical practice, education, and research; however, further discussion on the application of this theory in administration is needed. The authors in this article aim to substruct Watson's theory of human caring for nursing administration. Major elements of the theory—transpersonal caring dimensions, caring competencies, and caring moments—are presented in a model of substruction that links the theoretical basis to methodology. In conclusion, this theory can be used as a framework or a conceptual model in nursing administration within an organization.